2020
DOI: 10.1021/acssuschemeng.9b06569
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Surface Area, Graphene Quantum Dots, and Functional Groups for the Simple Acid-Treated Carbon Fiber Electrode of Flexible Fiber-Type Solid-State Supercapacitors without Active Materials

Abstract: Flexible fiber-type solid-state supercapacitors (FSCs) are demanded for energy storage of wearable soft electronics. A flexible carbon fiber (CF) with high electrical conductivity and good energy storage ability can act as the current collector and the active material simultaneously. Improving the energy storage ability of the CF without depositing active materials is highly promising to avoid active materials from peeling off, especially under bending conditions. In this study, the CF is treated with acid mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The surface changes of the carbon fibers after acid treatment were then analyzed by applying FTIR on the pristine and treated carbon clothes as shown in Figure S1 (Supporting Information). Compared to the pristine carbon cloth, some additional peaks are observed for the treated carbon cloth at about 1604 and 3679 cm –1 , which can be assigned to the CO stretching in carboxyl groups and O–H stretching of hydroxyl groups, respectively. It is suggested that due to the acid treatment of carbon cloth by HNO 3 and H 2 SO 4 , the carboxyl and hydroxyl groups are introduced on the surface of carbon fibers and thus result in the improved wettability with molten sodium, which is favorable for generating a sodium composite anode. A uniform diameter of the carbon fibers with smooth surfaces is observed with a diameter of about 10 μm as shown in Figure d–f.…”
Section: Resultsmentioning
confidence: 99%
“…The surface changes of the carbon fibers after acid treatment were then analyzed by applying FTIR on the pristine and treated carbon clothes as shown in Figure S1 (Supporting Information). Compared to the pristine carbon cloth, some additional peaks are observed for the treated carbon cloth at about 1604 and 3679 cm –1 , which can be assigned to the CO stretching in carboxyl groups and O–H stretching of hydroxyl groups, respectively. It is suggested that due to the acid treatment of carbon cloth by HNO 3 and H 2 SO 4 , the carboxyl and hydroxyl groups are introduced on the surface of carbon fibers and thus result in the improved wettability with molten sodium, which is favorable for generating a sodium composite anode. A uniform diameter of the carbon fibers with smooth surfaces is observed with a diameter of about 10 μm as shown in Figure d–f.…”
Section: Resultsmentioning
confidence: 99%
“…Highly flexible all‐solid‐state supercapacitors can also be prepared by incorporating GQDs and doped‐GQDs into the structure of supercapacitors. [ 246 ] Hsiao and Lin [ 247 ] proposed a simple acid treatment method, based on a mixture of HNO 3 and H 2 SO 4 acids, to fabricate highly flexible carbon fiber‐based all‐solid‐state stand‐alone supercapacitors without any additional active materials in the structure. They used the acid treatment with a specific acid ratio to not only generate GQDs from amorphous carbons in the structure of carbon fibers but also introduce required functional groups and improve the specific surface area of carbon fibers.…”
Section: Applications Of Gqdsmentioning
confidence: 99%
“…Qiu et al prepared a composite composed of histidine-functionalized GQDs and Ni-Co-layered double hydroxides, this time serving as a positive electrode in a prototype supercapacitor [ 209 ]; in this case, the device showed the maximum energy of 48.89 W h kg −1 at 0.80 kW kg −1 , as well as interesting cycling stability (91.13% after 6000 cycles), confirming similar results obtained by Ma and others [ 210 ]. Flexible fiber-type solid-state supercapacitors have been recently presented for wearable soft electronics based on carbon fiber, which is used as a tridimensional support and as a source of GQDs after degradation in the presence of HNO 3 /H 2 SO 4 [ 211 ]. The so-produced composite demonstrated high performance and high flexibility as well, with performance retention over 1000 bending cycles at 180°, up to 99.5% capacity.…”
Section: Gqd Applications In Energy-related Applicationsmentioning
confidence: 99%